The hidden structure : understanding nature through design - Lee, Yu Hui (2018)
Much of our seemingly chaotic and complex world is structured and grounded and logic and science. Nature is amazing in its ability to adapt and evolve to find the most efficient solution, and it has been doing so for the past 3.8 billion years. A knowledge and understanding of the structures formed in nature could be applied to other disciplines such as design and engineering to bring about greater sustainability for our society – this is known as biomimicry. Yet, this knowledge is not widespread and the presentation of its information do not seem to appeal to those outside the field of biology. Hence, this project seeks to explore ways to better present the amazing structure and potential of nature through the fundamentals of visual communication and information design, to bridge the gap between scientific knowledge and the audience.